2020
DOI: 10.1128/jcm.01913-19
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Clostridioides difficile Toxin Testing for Higher Diagnostic Accuracy

Abstract: Currently available diagnostic tests for Clostridioides difficile infection (CDI) lack specificity or sensitivity, which has led to guideline recommendations for multistep testing algorithms. Ultrasensitive assays for detection of C. difficile toxins provide measurements of disease-specific markers at very low concentrations. These assays may show improved accuracy compared to that of current testing methods and offer a potential standalone solution for CDI diagnosis, although large studies of clinical perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Unfortunately, the company decided not to pursue commercial application of the Clarity assay. However, these studies demonstrated the enhanced sensitivity of single-molecule counting technology for detection of free toxin in patient stool samples compared with standard EIAs [54,55 ▪ ,56].…”
Section: Future Diagnostic Approachesmentioning
confidence: 99%
“…Unfortunately, the company decided not to pursue commercial application of the Clarity assay. However, these studies demonstrated the enhanced sensitivity of single-molecule counting technology for detection of free toxin in patient stool samples compared with standard EIAs [54,55 ▪ ,56].…”
Section: Future Diagnostic Approachesmentioning
confidence: 99%
“…One of the challenges in diagnosing CDI is that of being able to distinguish between patients with true CDI and those who are colonized ( Planche and Wilcox, 2015 ). The search for new methods for the detection of C. difficile and for distinguishing true infection from colonization in diarrhea of other causes is ongoing ( Kelly et al., 2020 ; Sandlund et al., 2020 ; Ng et al., 2021 ). Profiling the microbiome and identifying possible microbiome biomarkers could help us differentiate between infection and colonization by C. difficile and diarrhea of other causes (NOCDI) ( Planche and Wilcox, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Those assays can detect disease-specific markers at extremely low concentrations with good accuracy. 89 However, these ultrasensitive immunoassays require further validation. 8,89 Glutamate dehydrogenase immunoassays identify a metabolic enzyme that is highly conserved and abundant in all C. difficile isolates.…”
mentioning
confidence: 99%
“…89 However, these ultrasensitive immunoassays require further validation. 8,89 Glutamate dehydrogenase immunoassays identify a metabolic enzyme that is highly conserved and abundant in all C. difficile isolates. Since GDH is found in both toxigenic and nontoxigenic isolates, this test lacks specificity and should be combined with another method (namely, toxin detection test).…”
mentioning
confidence: 99%